Digital hostility: contemporary crisis, disrupted belonging and self-care practices. (August 2022) - Cover, Rob
Digital hostility has verifiably increased over the past decades among adult users of social media and online forums. Both an extension of, and different from, cyberbullying, digital hostility has become a framing factor in the reduction of quality of public debate at a social level and, at an individual level, has been cited as responsible for withdrawal, disconnection and negative impact on health and mental health. This paper draws on digital ethnographic and in-depth survey research to present new approaches to understanding the cause, form and impact of digital hostility among adults. Participants in the study generated valuable discussion which, when analysed from the perspective of media and cultural theory, presented three significant findings: Firstly, that digital hostility is increasingly recognised not as a behavioural problem among individual perpetrators but as a 'crisis' that both arises from within and disrupts digital culture. Secondly, participants discussed the impact of their own experiences of online adversity on their health and wellbeing. Analysed through critical and cultural frameworks, their experiences can be understood as being positioned as ungrievable subjects or, in extreme cases, bare life—particularly when digital hostility is experienced through cross-platform trolling and spills over into stalking. Finally, participants discussed the experience of self-care in the absence of adequate support mechanisms by platform hosts. Self-care manifested not as individualised self-protection but as mutually-supportive, using alternative platforms to share strategies and support; care was also oriented towards care for digital culture more broadly. This paper provides initial insights into the perception and understanding of digital hostility as an everyday cultural experience.